Experiencing Sound Installations: A conceptual framework. Issue 2 (16th August 2022) - Fraisse, Valérian; Giannini, Nicola; Guastavino, Catherine; Boutard, Guillaume
Abstract : We propose a conceptual framework for describing and documenting sound installations from a visitor's point of view. In the form of a taxonomy, the framework includes four complementary perspectives: sound sources, sound design approaches, visiting modalities and visual aspects. Its elaboration was informed by a review of contemporary sound installations in Quebec as well as a literature review on conceptual and theoretical frameworks on sound art and sound installations. Compared with existing frameworks, the taxonomy is useful for describing and comparing sound installations across meaningful perspectives from a visitor's stance. To illustrate the potential benefits of the taxonomy and the diversity of installations it can portray, we provide a comparative analysis of four contemporary sound installations from different perspectives. We conclude with the use of this taxonomy for documentation purposes.